Transformational Leadership Communication in Developing Countries’ Business Environment - Miftari, Vehbi (Journal of History Culture and Art Research, 2018)
The paper investigates the role of the leaders of Small and Medium Enterprises (SME’s) in a Developing Countries’ Business Environment (DCBE). The research aims to underline the rapid transformation of this environment in transitional countries like Kosovo and other Balkan countries and the readiness of SME’s to adapt themselves in a new market economy. Again, the research aims to analyze whether the changing Business Environment has determined the transformation of the leadership skills and strategies of doing business and whether they have accepted the new role inside the SME’s and in a market. The SME leadership is facing with two challenging situations: the transition of the economy from state controlled system to open market economy, and the transformation of the organizational communication structure to a more active one. The research aims to identify the leaders’ forms and methods of communication in medium enterprises in transitional countries and to identify transformational leaders. The research objective is to have an overlook on leaders’ profile in medium enterprises in Kosovo. The research shows a clear picture about fundamental communication characteristics of leaders in SME’s and the possibilities of the transformation of the leaders from leading managers to transformational leaders.